Bi2MoO6 / UIO-66-NH2 photocatalytic composite material as well as preparation method and application thereof
Formed heterogeneous knots through BI2MOO6 and UIO-66-NH2, prepare BI2MOO6/UIO-66-NH2 photocatalytic composite materials, solve the weakness of light absorption and carrier transportation of BI2MOO6 photocatalyst when photocatalyst degradation pollutants. Poor problems have achieved efficient ammonia nitrogen degradation and photocatalytic activity.
Patent Information
- Application Number
- CN202411369974.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-24
AI Technical Summary
The existing Bi2MoO6 photocatalysts have problems such as weak light absorption, fast recombination, and poor photogenerated carrier transport when photocatalyzing the degradation of pollutants, which limits their application effect.
Bi2MoO6/UIO-66-NH2 photocatalytic composite materials are prepared by forming a heterojunction with UIO-66-NH2. The amine modification and large specific surface area of UIO-66-NH2 are used to inhibit the recombination of photogenerated electron-hole pairs and improve Photocatalytic performance.
The composite material shows good photocatalytic activity under visible light, which can effectively degrade ammonia nitrogen in the garbage filtration fluid, and has stability and high adsorption performance.
Smart Images

Figure CN119346172A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photocatalytic degradation, and specifically relates to a Bi2MoO6 / UIO-66-NH2 photocatalytic composite material and a preparation method and application thereof. Background Art
[0002] Landfill has been widely used as a method of treating urban solid waste at home and abroad. During the stacking and landfilling process, solid waste produces leachate due to compaction, fermentation and rainfall seepage. Leachate is a high-concentration organic wastewater, generally dark brown, containing a large amount of inorganic and organic pollutants. Its composition is mainly determined by the type and composition of the garbage, and changes with the age of the landfill. The water quality and quantity of leachate are unstable and the proportion of nutrient elements is unbalanced. At the same time, it contains a large amount of non-chlorinated aromatic compounds such as naphthalene and phenanthrene that are difficult to degrade, and toxic substances such as ammonia nitrogen, which are very difficult to treat. The treatment research of leachate has become a hot spot and difficulty in the field of environmental engineering at home and abroad. With the increase of landfill time, the concentration of ammonia nitrogen in leachate is getting higher and higher, and the removal of ammonia nitrogen has also become a major difficulty in the treatment of leachate.
[0003] Photocatalysis is a new type of efficient and green pollutant degradation method. In view of this, the development of efficient visible light-driven photocatalysts has become a research hotspot in recent years. 2- and [Bi2O2] 2+ As a typical metallographic oxide semiconductor, the structure of bismuth molybdate (Bi2MoO6) composed of layers promotes the photocatalytic degradation of pollutants. Bi2MoO6 responds to visible light due to its narrow band gap of 2.5-2.8eV. However, Bi2MoO6 has weak light absorption, fast recombination, and poor transport of photogenerated carriers, which greatly limits its application in photocatalytic degradation of pollutants.
[0004] Metal-organic frameworks, as an emerging material, have been widely used due to their advantages such as large specific surface area, adjustable structure, and abundant active sites. MOF-based photocatalysts include Zr-MOF, which is widely used due to its thermal stability and structural stability under aqueous conditions. As a type of Zr-MOF, UIO-66-NH2 not only has the excellent properties of other MOFs, but also has a strong visible light utilization rate due to its amine modification. However, the rapid recombination of photoexcited carriers limits its photocatalytic performance. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention provides a Bi2MoO6 / UIO-66-NH2 photocatalytic composite material and its preparation method and application. The present invention finds through research that UIO-66-NH2 is suitable for forming a heterojunction with Bi2MoO6 to solve their respective shortcomings and thus improve the photocatalytic performance. The composite material effectively inhibits the recombination of photogenerated electron-hole pairs, has good visible light photocatalytic activity, and also has a large specific surface area.
[0006] The present invention is achieved through the following technical solutions:
[0007] A Bi2MoO6 / UIO-66-NH2 photocatalytic composite material comprises Bi2MoO6 and UIO-66-NH2, wherein the mass ratio of the Bi2MoO6 to the UIO-66-NH2 is 7:3, 1:1 or 3:7.
[0008] Preferably, in the composite material, UIO-66-NH2 is loaded on the surface of Bi2MoO6 to form a regular flower-like structure.
[0009] The preparation method of the Bi2MoO6 / UIO-66-NH2 photocatalytic composite material comprises the following steps:
[0010] Step 1) dissolving UIO-66-NH2 in anhydrous ethanol and ultrasonically treating for 30 min to form a uniformly dispersed solution as solvent A;
[0011] Step 2) Bi(NO3)3·5H2O and NaMoO4·2H2O were added to the ethylene glycol solution and stirred at room temperature for 20 min as solvent B;
[0012] Step 3) adding the solvent B prepared in step 2) dropwise to the solvent A prepared in step 1) in proportion, and stirring the resulting mixture at room temperature for 30 min;
[0013] Step 4) transferring the mixed solution obtained in step 3) into a reaction vessel, reacting at 160° C. for 12 h, and cooling to room temperature;
[0014] Step 5) The solid obtained from the solution of step 4) is collected by centrifugation and washed several times with anhydrous ethanol and ethylene glycol;
[0015] Step 6) Dry the product obtained in step 5) in a vacuum oven at 80°C to obtain the product.
[0016] Preferably, the preparation method of UIO-66-NH2 in step 1) is as follows:
[0017] Add 2-aminoterephthalic acid and ZrCl4 into DMF solution, completely dissolve them by ultrasonication, and then add acetic acid; transfer the solution to a reactor, heat it at 120°C for 24 hours, and then wait for it to cool to room temperature; collect it after washing and drying to obtain the product.
[0018] The preparation method of the Bi2MoO6 / UIO-66-NH2 photocatalytic composite material comprises the following steps:
[0019] Step A) Bi(NO3)3·5H2O and NaMoO4·2H2O are added to an ethylene glycol solution and stirred at room temperature for 20 minutes, and then heated, washed, dried and collected to obtain Bi2MoO6;
[0020] Step B) adding 2-aminoterephthalic acid and ZrCl4 to a DMF solution, dissolving them completely by ultrasonication, and then adding acetic acid thereto; transferring the solution to a reaction kettle, heating it continuously at 120° C. for 24 hours, and then waiting for cooling to room temperature; collecting it after washing and drying to obtain UIO-66-NH2;
[0021] Step C) Grind the Bi2MoO6 prepared in step A) and the UIO-66-NH2 prepared in step B) into powders, and mix them according to proportions to obtain.
[0022] The above-mentioned Bi2MoO6 / UIO-66-NH2 photocatalytic composite material, or the Bi2MoO6 / UIO-66-NH2 photocatalytic composite material prepared by the above-mentioned preparation method is used in treating organic wastewater.
[0023] Preferably, the organic wastewater is landfill leachate.
[0024] The above-mentioned Bi2MoO6 / UIO-66-NH2 photocatalytic composite material, or the application of the Bi2MoO6 / UIO-66-NH2 photocatalytic composite material prepared by the above-mentioned preparation method in the degradation of ammonia nitrogen.
[0025] The beneficial effects of the present invention are as follows:
[0026] The present invention utilizes a simple solvent thermal method to prepare a Bi2MoO6 / UIO-66-NH2 photocatalytic composite material, the morphology of which is a regular flower-like structure. The material has the advantages of high adsorption and photocatalytic performance, good stability, etc. It has been tested that it can effectively degrade ammonia nitrogen in landfill leachate and is suitable for popularization and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 XRD images of Bi2MoO6, UIO-66-NH2 and BUN-30 in Example 1;
[0028] Figure 2 FT-IR image curves of Bi2MoO6, UIO-66-NH2 and BUN-30 in Example 1;
[0029] Figure 3 SEM images of UIO-66-NH2 (a), Bi2MoO6 (b), and BUN-30 (c) in Example 1, and EDS mapping images of N (d), O (e), Zr (f), Mo (g), and Bi (h);
[0030] Figure 4 XPS images of BUN-30 in Example 1: (a) C1s; (b) N1s; (c) O1s; (d) Bi 4f; (e) Mo 3d; (f) Zr 3d;
[0031] Figure 5 The UV-visible spectra (a) and band gaps (b), XPS valence band spectra (c) and PL spectra (d) of the Bi2MoO6, UIO-66-NH2 and BUN-30 nanohybrid materials in Example 1;
[0032] Figure 6 This is a diagram showing the ammonia nitrogen degradation efficiency of landfill leachate treated with Bi2MoO6, UIO-66-NH2 and BUN-30 in Example 2. DETAILED DESCRIPTION
[0033] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0034] Unless otherwise specified, the technical means used in the following examples are all conventional means well known to those skilled in the art, and the experimental methods without specifying the specific conditions are all conventional methods in the art.
[0035] Example 1 Preparation and Analysis of Bi2MoO6 / UIO-66-NH2
[0036] 1. Preparation of Bi2MoO6 / UIO-66-NH2 photocatalytic composite material, the specific steps are as follows:
[0037] (1) Preparation of UIO-66-NH2 by solvothermal method
[0038] Add appropriate amount of 2-aminoterephthalic acid and ZrCl4 to DMF solution, completely dissolve by ultrasonication, and then add appropriate amount of acetic acid; transfer the solution to a stainless steel reactor, heat it continuously at 120°C for 24 hours, and then wait for it to cool to room temperature; wash it with ethanol and water several times to remove excess impurities, and collect it after vacuum drying at 80°C to obtain.
[0039] (2) An appropriate amount of UIO-66-NH2 was dissolved in anhydrous ethanol and ultrasonically treated for 30 min to form a uniformly dispersed solution, which was used as solvent A (UIO-66-NH2 solution).
[0040] (3) Add appropriate amounts of Bi(NO3)3·5H2O and NaMoO4·2H2O into the ethylene glycol solution and continue stirring at room temperature for 20 min as solvent B (Bi2MoO6 solution).
[0041] (4) An appropriate amount of solvent B was added dropwise to solvent A, and the resulting mixture was stirred at room temperature for 30 min.
[0042] (5) The mixed solution was transferred to a stainless steel reactor, reacted at 160 °C for 12 h, and cooled to room temperature.
[0043] (6) The solid was collected from the mixed solution by centrifugation and washed several times with anhydrous ethanol and ethylene glycol.
[0044] (7) The product was dried in a vacuum oven at 80 °C to obtain the Bi2MoO6 / UIO-66-NH2 composite material.
[0045] In the above preparation steps, the mass ratios of Bi2MoO6 and UIO-66-NH2 are 7:3, 1:1, and 3:7, respectively, and the prepared photocatalytic composite materials Bi2MoO6 / UIO-66-NH2 are recorded as BUN-30, BUN-50, and BUN-70, respectively. Subsequent experiments show that the photocatalytic performance of BUN-30 exceeds that of BUN-50 and BUN-70, so BUN-30 is used as the research object.
[0046] 2. Test and analyze Bi2MoO6, UIO-66-NH2 and the prepared photocatalytic composite material BUN-30, as follows:
[0047] (1) The crystal phase of the material was recorded using a D / MAX2500 diffractometer (Rigaku, Japan) to obtain X-ray diffraction (XRD) patterns. Figure 1 As shown, compared with the standard card, the characteristic peaks of the original Bi2MoO6 are located at 2θ=10.8°, 23.7°, 28.4°, 32.6°, 46.9°, and 55.6°, corresponding to the (020), (111), (131), (200), (260), and (331) planes, respectively. Figure 1The results show the successful preparation of Bi2MoO6; and the diffraction peaks of UIO-66-NH2 are consistent with the published XRD patterns of UIO-66-NH2; in contrast, the XRD pattern of the BUN-30 hybrid material is similar to that of Bi2MoO6, and the additional characteristic peaks of UIO-66-NH2 are relatively weak, which is due to the fact that the Bi2MoO6 nanosheets encapsulate UIO-66-NH2 or the amount of UIO-66-NH2 is small. In addition, the characteristic peaks of the (131) surface of the BUN-30 hybrid material are broader and less intense than those of the monomer Bi2MoO6, proving that the addition of UIO-66-NH2 inhibits the growth of Bi2MoO6 nanoflowers.
[0048] (2) Fourier transform infrared (FT-IR) spectra were plotted using a Spectrum One FTIR spectrophotometer (PerkinElmer, USA). Figure 2 As shown in the spectrum of Bi2MoO6, 557, 731 and 842 cm -1 The absorption peaks at 479 cm-1 belong to the stretching vibration of Bi-O bond, the asymmetric stretching vibration of MoO6 and the stretching vibration of Mo-O-Mo bond; for UIO-66-NH2, 479 cm-1 -1 The peaks at 664 and 767 cm are Zr-O asymmetric stretching vibrations; -1 The peaks at 1383, 1433 and 1618 cm-1 can be attributed to the vibration of the CH and OH bonds of the H2ATA ligand. -1 The peaks at 1383, 1433, and 1618 cm-1 may belong to the symmetric and asymmetric stretching vibrations of the carboxyl group. Due to the addition of a small amount of UIO-66-NH2, the FTIR pattern of BUN-30 is similar to that of Bi2MoO6. In the BUN-30 spectrum, it can be observed that UIO-66-NH2 has peaks at 1383, 1433, and 1618 cm-1. -1 The peak at.
[0049] The above XRD and FT-IR results indicate that hybrid materials were successfully formed between Bi2MoO6 and UIO-66-NH2.
[0050] (3) Use transmission electron microscopy (TEM) and scanning electron microscopy (SEM) combined with energy dispersive spectroscopy (EDS) to analyze the microscopic morphology, such as Figure 3 shown.
[0051] from Figure 3 In (a), it can be seen that the bulk MOF materials aggregate together, and UIO-66-NH2 aggregates into clusters; Figure 3 In (b), we can see that the monomer Bi2MoO6 presents a flower-like structure; Figure 3(c) is a local magnified SEM image of the BUN-30 material, which can be used to analyze the morphology of the material in more depth: the flower-like Bi2MoO6 grows on the surface of the block UIO-66-NH2, which effectively enhances the roughness of the composite material, adds more active sites, and strengthens the photocatalytic performance. The corresponding element mapping spatial distribution of the sample and the relative abundance of a single element are shown in Figure 2. Figure 3 As shown in (d)-(h), it is clear that the distribution of elements in the BUN-30 composite is dispersed and uniform, which also shows that the BUN-30 composite is not just a physical mixture.
[0052] (4) X-ray photoelectron spectroscopy (XPS) analysis of chemical composition and valence state was performed using an ESCALAB 250Xi analyzer, such as Figure 4 As shown, the measured spectrum shows the presence of Bi, Mo, O, Zr, C and N elements in the BUN-30 composite material.
[0053] like Figure 4 As shown in (a), the C1s spectrum of BUN-30 is divided into three peaks, located at 284.6 eV, 286.2 eV and 288.5 eV, corresponding to the CC (or CH), CO and OCO groups of NH2-BDC, respectively. Figure 4 As shown in (b), the peak at 399.2 eV may belong to the -NH2 of the N element in UIO-66-NH2. Figure 4 As shown in (c), the high-resolution O1s spectrum can be fitted to two peaks at 530.2 eV and 531.3 eV, which are attributed to the lattice oxygen of BUN-30 and the Bi-O or Zr-O bonds, respectively. Figure 4 As shown in (d), the Bi 4f peaks of BUN-30 at 159.1eV and 164.4eV are respectively attributed to Bi 3+ Bi 4f 7 / 2 and Bi4f 5 / 2 , indicating that the spectrum peaks of Bi2MoO6 are concentrated at 159.1eV and 164.4eV. Figure 4 As shown in (e), BUN-30 should be Mo 3d at 232.4eV and 235.5eV. 5 / 2 and Mo 3d 3 / 2 The binding energy of the peak indicates that the valence state of Mo is +6, which is higher than that of Mo in Bi2MoO6. Figure 4 As shown in (f), compared with UIO-66-NH2, the Zr 3d 5 / 2 and Zr 3d 3 / 2The peaks are centered at 182.7 eV and 185.1 eV, respectively, shifting toward lower binding energies. Obviously, the binding energies of Bi 4f and Mo 3d in BUN-30 are higher than those in Bi2MoO6, and the binding energy of Zr 3d in BUN-30 is lower than that in UIO-66-NH2. This may be because the electron density of Zr is higher, while that of Bi and Mo is lower, indicating the presence of a heterogeneous structure in BUN-30.
[0054] The above XPS results verify the existence of strong chemical interaction between Bi2MoO6 and UIO-66-NH2.
[0055] (5) Ultraviolet-visible (Uv-vis) diffuse reflectance spectroscopy (DRS) was recorded using Shimadzu Uv-2550, and the optical properties of the samples were evaluated using UV-vis DRS, such as Figure 5 shown.
[0056] like Figure 5 As shown in (a), the parent UIO-66-NH2 has an absorption edge at about 447nm, which indicates that UIO-66-NH2 can receive visible light, but the visible light receiving range is relatively limited; Bi2MoO6 has a wider absorption edge at about 526nm, showing a higher absorption intensity in the visible light region. And due to the successful formation of the heterojunction, the response area of BUN-30 has a slight red shift relative to Bi2MoO6, which can absorb more visible light energy.
[0057] The band gap energy (Eg) is calculated using the following formula:
[0058] (αhv) (1 / n) =A(hv-Eg)
[0059] In the formula: α is the absorption coefficient, hν is the energy, A is a constant value, and n = 1 / 2.
[0060] like Figure 5 As shown in (b), the energy bands of Bi2MoO6 and UIO-66-NH2 are 2.66eV and 2.46eV respectively. Figure 5 As shown in (c), the valence band positions of Bi2MoO6 and UIO-66-NH2 are 2.38eV and 3.28eV, respectively.
[0061] The photoelectron-hole recombination rate of BUN-30 material was analyzed by fluorescence spectroscopy. The stronger the fluorescence signal, the higher the electron-hole recombination rate, which also means a decrease in the photocatalytic degradation efficiency. Figure 5As can be seen in (d), at 450nm, the fluorescence signal of UIO-66-NH2 is higher, and Bi2MoO6 shows a quenched fluorescence signal, which indicates that the photoinduced electron-hole recombination rate of UIO-66-NH2 is higher and Bi2MoO6 has a certain resistance to visible light excitation. In addition, the fluorescence intensity of the UIO-66-NH2 modified Bi2MoO6 composite material BUN-30 is reduced, confirming that it has excellent photocatalytic activity, which matches the experimental results.
[0062] Example 2 Application of Bi2MoO6 / UIO-66-NH2
[0063] The photocatalytic composite materials Bi2MoO6 / UIO-66-NH2 and Bi2MoO6 and UIO-66-NH2 prepared in Example 1 were used to degrade landfill leachate, and their adsorption and photodegradation performances of ammonia nitrogen were studied, as follows:
[0064] 1. Experimental steps
[0065] Before the photocatalytic experiment, the impurities in the landfill leachate were removed by filtration, and then the extracted solution was diluted 10 times as the research object. At room temperature, 20 mg of Bi2MoO6, UIO-66-NH2 and the photocatalytic composite material Bi2MoO6 / UIO-66-NH2 were added to 50 mL of landfill leachate solution, respectively, and stirred for 1 h in the dark to ensure the balance of adsorption and desorption. Then, stirring was continued for 1.5 h under a 300W xenon lamp, and a small amount of supernatant was taken out regularly. The supernatant was drawn with a disposable syringe equipped with a 0.45μm organic microporous filter membrane, and the catalyst was separated by high-speed centrifugation. The ammonia nitrogen degradation rate was determined using an online ammonia nitrogen detector.
[0066] 2. Experimental results
[0067] The degradation rate of ammonia nitrogen in landfill leachate by the flower-shaped Bi2MoO6 / UIO-66-NH2 photocatalytic composite material prepared in Example 1 was significantly higher than that of Bi2MoO6 and UIO-66-NH2 when illuminated by xenon lamp for 1.5 hours after dark adsorption for 1 hour, especially BUN-30, whose degradation rate can reach 72.4%, while the degradation rates of BUN-50 and BUN-70 are 48.3% and 46.6%, respectively. Figure 6 As shown, under the same reaction conditions, the degradation efficiency of ammonia nitrogen by BUN-30 is 2.5 times that of Bi2MoO6 and 4 times that of UIO-66-NH2.
[0068] The experimental results of the above embodiments show that the combination of high-porosity UIO-66-NH2 and Bi2MoO6 with appropriate band gap not only improves the adsorption capacity, but also effectively separates photoelectron holes, thereby enhancing the adsorption capacity, capacity and photocatalytic activity of the Bi2MoO6 / UIO-66-NH2 photocatalytic composite material.
[0069] In addition, by simply grinding and mixing Bi2MoO6 powder and UIO-66-NH2 powder together (mass ratio of 3:7), under the same reaction conditions, the ammonia nitrogen degradation efficiency is about 50%, which is not as good as the composite material prepared in Example 1. It can be seen that the composite material prepared by the solvothermal method is more effective than the material after simple physical mixing, which can prove that the material prepared by the solvothermal method has stronger photocatalytic performance.
[0070] The embodiments described above are only some embodiments of the present invention, rather than all embodiments. The detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. The scope of protection of the present invention shall be subject to the scope required by the claims. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work shall fall within the scope of protection of the present invention.
Claims
1. A Bi2MoO6 / UIO-66-NH2 photocatalytic composite material, characterized in that: It includes Bi2MoO6 and UIO-66-NH2, and the mass ratio of Bi2MoO6 to UIO-66-NH2 is 7:3, 1:1 or 3:
7.
2. The Bi2MoO6 / UIO-66-NH2 photocatalytic composite material according to claim 1, characterized in that: In the composite material, UIO-66-NH2 is loaded on the surface of Bi2MoO6 to form a regular flower-like structure.
3. The method for preparing the Bi2MoO6 / UIO-66-NH2 photocatalytic composite material according to claim 2, characterized in that: The following steps are involved: Step 1) dissolving UIO-66-NH2 in anhydrous ethanol and ultrasonically treating for 30 min to form a uniformly dispersed solution as solvent A; Step 2) Bi(NO3)3·5H2O and NaMoO4·2H2O were added to the ethylene glycol solution and stirred at room temperature for 20 min as solvent B; Step 3) adding the solvent B prepared in step 2) dropwise to the solvent A prepared in step 1) in proportion, and stirring the resulting mixture at room temperature for 30 min; Step 4) Transfer the mixed solution obtained in step 3) to a reactor, react at 160° C. for 12 hours, and cool to room temperature; Step 5) Collect the solid from the solution obtained in step 4) by centrifugation, and wash it several times with anhydrous ethanol and ethylene glycol; Step 6) Dry the product obtained in step 5) in a vacuum oven at 80° C. to obtain the product.
4. The method for preparing a Bi2MoO6 / UIO-66-NH2 photocatalytic composite material according to claim 3, characterized in that: Step 1) The preparation method of UIO-66-NH2 is as follows: Add 2-aminoterephthalic acid and ZrCl4 into DMF solution, completely dissolve them by ultrasonication, and then add acetic acid; transfer the solution to a reactor, heat it at 120°C for 24 hours, and then wait for it to cool to room temperature; collect it after washing and drying to obtain the product.
5. The method for preparing the Bi2MoO6 / UIO-66-NH2 photocatalytic composite material according to claim 1, characterized in that: The following steps are involved: Step A) Bi(NO3)3·5H2O and NaMoO4·2H2O are added to an ethylene glycol solution and stirred at room temperature for 20 minutes, and then heated, washed, dried and collected to obtain Bi2MoO6; Step B) adding 2-aminoterephthalic acid and ZrCl4 to a DMF solution, dissolving them completely by ultrasonication, and then adding acetic acid thereto; transferring the solution to a reaction kettle, heating it continuously at 120° C. for 24 hours, and then waiting for cooling to room temperature; collecting it after washing and drying to obtain UIO-66-NH2; Step C) Grind the Bi2MoO6 prepared in step A) and the UIO-66-NH2 prepared in step B) into powders, and mix them according to proportions to obtain.
6. Use of the Bi2MoO6 / UIO-66-NH2 photocatalytic composite material as described in claim 1 or 2, or the Bi2MoO6 / UIO-66-NH2 photocatalytic composite material prepared by the preparation method according to any one of claims 3 to 5 in treating organic wastewater.
7. The use according to claim 6, characterized in that: The organic wastewater is landfill leachate.
8. Use of the Bi2MoO6 / UIO-66-NH2 photocatalytic composite material as described in claim 1 or 2, or the Bi2MoO6 / UIO-66-NH2 photocatalytic composite material prepared by the preparation method according to any one of claims 3 to 5 in the degradation of ammonia nitrogen.